COMPARISON BETWEEN SEVERAL OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY DEVICES AND INDOCYANINE GREEN ANGIOGRAPHY OF CHOROIDAL NEOVASCULARIZATION. Issue 5 (May 2020) - Corvi, Federico; Cozzi, Mariano; Barbolini, Erika; Nizza, Dario; Belotti, Maria; Staurenghi, Giovanni; Giani, Andrea
Abstract : Purpose: To compare indocyanine green angiography and four different optical coherence tomography angiography (OCTA) devices and to test their reproducibility in the evaluation of choroidal neovascularization (CNV). Methods: This study was an observational case series of Type 1 and Type 2 CNV presenting at the Eye Clinic, Department of Biomedical and Clinical Sciences, Luigi Sacco Hospital, University of Milan, imaged with indocyanine green angiography and four different OCTA devices: prototype PlexElite (Carl Zeiss Meditec), prototype Spectralis OCTA (Spectralis; Heidelberg Engineering, Heidelberg, Germany), Optovue RTVue XR Avanti (Optovue, Inc, Fremont, CA), and AngioPlex (Cirrus 5000 HD-OCT; Carl Zeiss Meditec, Inc, Dublin, CA). Optical coherence tomography angiography examinations were performed using a 3 × 3-mm or 6 × 6-mm volume scan pattern to capture the full lesion. The mean area of CNV, vessel density, and fractal dimension were compared between the devices. Results: Seventeen eyes of 17 patients with CNV were enrolled. The CNV area was significantly larger in indocyanine green angiography than in the OCTA devices. Moreover, the four different instruments produced measurements with different mean values of CNV area, vessel density, and fractal dimension. The Bland–Altman analysis revealed that the limits of agreement for the comparisons were not acceptable. Conclusion: The choroidal neovascularization area is larger when imaged with standard indocyanine green angiography than with different OCTA devices with different algorithms, wavelengths, and scan patterns. The differences between several OCTA devices in the evaluation of quantitative parameters of CNV, such as CNV area, vessel density, and fractal dimension, suggest the necessity to standardize OCTA measurements for research and clinical practice. Abstract : The area of choroidal neovascularization is larger in indocyanine green angiography than in optical coherence tomography angiography. Several optical coherence tomography angiography devices provide different values of choroidal neovascularization parameters, suggesting the necessity to standardize optical coherence tomography angiography measurements.